2011
DOI: 10.1210/en.2010-0871
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Selective, Testosterone-Independent Remodeling of Dendrites in Gonadotropin-Releasing Hormone (GnRH) Neurons Prepubertally in Male Rats

Abstract: Adult GnRH neurons exhibit a stereotypic morphology with a small soma, single axon, and single dendrite arising from the soma with little branching. The adult morphology of GnRH neurons in mice reflects an anatomical consolidation of dendrites over postnatal development. We examined this issue in rat GnRH neurons with biocytin filling in live hypothalamic slices from infant males, as adult littermates and in gonad-intact males, castrated males, and in males with one of three levels of testosterone (T) treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In dnFGFR males, OS housing induces a significant shift of GnRH neuronal morphology toward a more mature distribution by PND100. This indicates that OS housing is not merely important for the rescue of number of GnRH neurons; it also participates in their anatomical remodeling, which correlates with GnRH neurons' ability to receive excitatory inputs (11,62). The differences between the genotypes disappeared by PND200, suggesting the remodeling defect in dnFGFR mice represents only a delay, not an absence, of dendritic pruning.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In dnFGFR males, OS housing induces a significant shift of GnRH neuronal morphology toward a more mature distribution by PND100. This indicates that OS housing is not merely important for the rescue of number of GnRH neurons; it also participates in their anatomical remodeling, which correlates with GnRH neurons' ability to receive excitatory inputs (11,62). The differences between the genotypes disappeared by PND200, suggesting the remodeling defect in dnFGFR mice represents only a delay, not an absence, of dendritic pruning.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to the former, the postnatal changes in GnRH neuronal morphology have been correlated with the functional maturation of the GnRH system (11,62). During puberty, dendritic pruning increases the proportion of unipolar neurons and decreases that of complex neurons (11,62).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the location of the GnRH neuron axon is presently unclear. As the processes that emanate from GnRH neuron soma often become thin in diameter, some laboratories have defined the thinnest process as the axon (Ybarra et al, 2011). However, previous work from our laboratory has demonstrated that, when cells are filled with biocytin in brain slices and post hoc reconstructed, processes containing dendritic spines and a dendritic morphology can easily be identified, but not axon-like processes (Campbell et al, 2005(Campbell et al, , 2009Cottrell et al, 2006;Herde et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…They synthesize GnRH peptide that is released from their nerve terminals in the median eminence to regulate luteinizing and folliclestimulating hormone release from the anterior pituitary and thus reproductive function (Moenter et al, 2003;Herbison, 2006). In adult mice, GnRH neurons are most commonly unipolar or bipolar with very long, unbranched dendritic processes (Campbell et al, 2005;Ybarra et al, 2011). While the long thin processes emanating from the cell body of most GnRH neurons possess spines and have a dendritic morphology (Jennes et al, 1985;Wray and Hoffman, 1986;Campbell et al, 2005Campbell et al, , 2009Cottrell et al, 2006), the origin of the GnRH neuron axon remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological reconstructions of GnRH neurons in acute brain slices have revealed that these dendrites project for large distances in the brain [10,11,12]. Further studies have revealed that this simple dendritic morphology is acquired over the course of puberty, since the morphology of GnRH neurons reconstructed from rodents before puberty is significantly more complex, with many more dendritic branches [13,14]. …”
Section: Gnrh Neuron Projections: Long and Spinymentioning
confidence: 99%